ANALISIS KEPUASAN KONSUMEN RESTORAN CEPAT SAJI MENGGUNAKAN METODE PARTIAL LEAST SQUARE (Studi Kasus: Burger King Bali) - SANJIWANI, MADE; JAYANEGARA, KETUT; KENCANA, I PUTU EKA N. (E-Jurnal Matematika, 2015)
The were two aims of this research. First is to get model of the relation between the latent variable quality of service and product quality to customer satisfaction. The second was to determine the influence of service quality on customer satisfaction and the influence of product quality on consumer satisfaction at Burger King Bali. This research implemented Partial Least Square method with 3 second order variables is the service quality, product quality, and customer satisfaction. In this research also used 5 first order variables to explain the variable service quality are tangibles, empathy, reliability, responsiveness, assurance and 6 first order variables to explain the variable quality product are performance, reliability, feature, durability, conformance, and design. Samples used in this research is 100. The results of this research indentify that the service quality and product quality affect customer satisfaction at Burger King.
Keywords: Customer Satisfaction; Partial Least Square (PLS); Products Quality; Quality of Service